Intercultural Challenges in Offshore Software Development Outsourcing Relationship: An Empirical Study: Intercultural Challenges in Offshore Software Development - Khan, Siffat Ullah; Azeem, Muhammad Ilyas (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The importance of intercultural challenges is recognized by both the practitioners and researchers in offshore software development outsourcing (OSDO) relationships. These challenges affect almost all the activities involved in offshore software development outsourcing relationships especially communication, mutual understanding, interpretation and decision making processes etc. which in turn leads to project failure. In our previous published study we identified, through systematic literature review (SLR), various intercultural challenges faced by vendors in OSDO relationship. The aim of this study was to validate these findings through industry practitioners and to identify its intensity as well as to identify any other intercultural challenges, faced by vendor organizations in OSDO relationships. We performed questionnaire surveys with 41 experts from different software companies. A seven point likert scale was used to determine the significance of each intercultural challenge. Our findings indicate that all the intercultural challenges are critical for OSDO vendors. We further analyzed these challenges based on different variables, such as company size, company type, expert’s job/position etc. We have identified that there is no significant difference in the intercultural challenges based on company type and expert’s experience level. We identified that “language and language proficiency” is the most commonly agreed and “difference in social behaviour” is the most commonly disagreed intercultural challenge in the category of both sizes of company. Similarly “language and language proficiency” is the most commonly agreed challenge based on experts job positions.